Importance of horizontally loaded movements to sports performance. - Zweifel, M. (Strength and Conditioning Journal, 2017)
The use of vertically loaded exercises, such as the back squat, deadlift, and olympic-style lifts, are commonly prescribed by strength and conditioning professionals to enhance the physical qualities of athletes. These methods have been supported as effective means, mainly for novice subjects, but their effectiveness and transfer has been questioned in more advanced athletes and in transfer to specific physical qualities. The effectiveness of vertically loaded exercise to enhance sprinting speed and change of direction (cod) speed is equivocal in advanced athletes, and the use of horizontally loaded movement may have better transfer for sprinting speed and cod speed.